Identification of hypoxically inducible mRNAs in HeLa cells using differential-display PCR. Role of hypoxia-inducible factor-1. - O'Rourke, J; Pugh, C; Bartlett, S; Ratcliffe, P (1996)
Oxygen is an important regulator of gene expression in mammalian cells, though the extent of operation and the organization of the inducible mechanisms involved are still largely undetermined. To define better the response to hypoxia, we have used differential display PCR to identify genes whose expression is induced in HeLa cells exposed to 1% oxygen. Among six genes whose induction by hypoxia was newly defined in this way, three were of known function, encoding the glucose transporter isoform 3 (Glut-3), adenylate kinase isoenzyme 3 (AK-3), and tissue factor, two were expressed sequence tags (ESTs), and one corresponded to a new sequence. One regulator of the transcriptional response to hypoxia has recently been identified as a heterodimeric DNA-binding complex termed hypoxia-inducible factor-1 (HIF-1), which is also inducible by the iron chelator, desferrioxamine. Of the six hypoxically regulated genes, at least four were also induced by exposure of the cells to desferrioxamine. To analyse further the mechanisms underlying induction of the genes identified in the differential display, inducible expression was compared in wild-type mouse hepatoma cells (Hepa-1), and mutant derivatives (c4) which fail to generate HIF-1, due to a functional defect in one component, HIF-1 beta. Two types of response were defined. For Glut-3 and AK-3, mutant (c4) cells showed almost complete loss of the inducible response to both hypoxia and desferrioxamine. In contrast, tissue factor mRNA was more inducible by both stimuli in c4 than wild-type cells. These studies demonstrate the critical importance of HIF-1 beta in newly recognized responses to hypoxia, and provide further evidence of the importance of this system of gene regulation in mammalian cells; they also demonstrate responses to both hypoxia and desferrioxamine which are independent of HIF-1 beta and which appear exaggerated in HIF-1 beta-deficient cells.